Translational functions of book illustrations, and what dickens has to do with them - Pereira, Nilce M. (De Gruyter, 2021)
This article examines book illustration from the perspective of translation studies-as intersemiotic translation. It is suggested that while illustrations can operate in multiple ways-as clarification, adornment, addition, and so on-as translations they should be thought of in terms of two different types of function that they fulfil in the literary work. The main function of illustrations, their primary function, is to render the text from the verbal into the visual medium. Other secondary functions that the pictures may perform will then be dependent on how the primary function has been accomplished; that is, on whether the pictures translated the text in such a way as to clarify it, add to it, or even contradict or deviate from its purposes. The illustrations in three of Dickens's novels will be used to exemplify these points.
Keywords: Book illustration; Dickens's novels; Functions